Ж.ИЗБАСҚАНОВ ШЫҒАРМАЛАРЫНДА ТЫРНАҚШАНЫҢ ҚОЛЛАНЫЛЫЎЫ - Казымбетова, З.М. (FAN va JAMIYAT, 2021)
In fiction, quotation marks are used to indicate that the word is in the reverse, figurative sense, that the thought expressed in the text belongs to someone else. This methodologically requires research in the linguopoetic aspect. Quotation marks form imagery, a comparative meaning in a sentence.